Laboratory Test of Scour Under Ice: Data and Preliminary Results - Hains, Decker; Zabilansky, Leonard (2004)
An ice cover may be a major factor determining how alluvial channel morphology evolves in rivers, and a significant influence on bridge pier scour. This was confirmed with real-time monitoring of the bed elevation and extensive bathymetry measurements made in the Mississippi River, the Missouri River, and the White River in Vermont. In all cases, the sediment process was significantly different from what existing sediment equations would predict. This laboratory study examined the sensitivity of various parameters affecting sediment transport under ice. Twenty tests were conducted in CRREL's refrigerated flume using mean flow velocities in the clear-water scour range. Three surface conditions were modeled: open water, a floating cover, and a fixed cover, simulating ice frozen to the river banks and a bridge pier, with a superimposed hydrostatic head that could be created by an upstream ice jam. The ice cover was simulated using Styrofoam with both smooth and rough surfaces. Under clear-water scour, the equilibrium scour depths for the fixed and floating covers were similar, but up to 21% higher than those found for open water. The cover roughness altered the velocity distribution and caused live-bed scour even when the mean flow velocity was 0.86 times the critical velocity for bed movement. When the average velocity was 0.93 times critical velocity, the pressure flow caused live-bed scour. A combination of increased cover roughness and pressure flow resulted in the largest equilibrium scour depth.